New records of rare and little-known species of angiosperm plants in the flora of the Crimea - V. V. Fateryga; A. V. Fateryga (Acta Biologica Sibirica, 2018)
The data on noteworthy records of five species are reported: new localities within the peninsula are provided for Allium regelianum and Frankenia pulverulenta; Ornithogalum arcuatum and Phelipanche arenaria are confirmed for the flora of the Crimea; Tetradiclis tenella was found by us after 94 years since its previous collection.